1975
DOI: 10.1161/01.str.6.2.188
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Blood Flow in Cats After an Acute Hypertensive Insult With Damage to the Blood-Brain Barrier

Abstract: Xenon clearance method in anesthetized cats under controlled ventilation. An acute pressure increase in the carotid system increases the cerebrovascular permeability to Evans blue, indicating damage to the blood-brain barrier. In these conditions the reactivity of cerebral blood vessels toward changes in the acid-base balance is altered: the CO 2 reactivity is less pronounced, while the effect of increasing the plasma [HCO 3 ] is more pronounced than in normal cats. Autoregulatory capacity toward moderate alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1976
1976
1990
1990

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The fact that p C 0~induced changes in cerebral extracellular pH readily influences the CBF in normal conditioas whereas changes in plasma bicarbonate at constant pCO2 do not, is probably related to the fact that CO, readily crosses the endothelid membrane whereas H and HCOacannot freely cross the intact blood-brain barrier. It has been demonstrated, however, that hypercapnia, o'r, in particular, damage to the blood-brain barrier induced by acute hypertension in cats, results in an increased reactivity of the cerebral blood flow to changes in the plasma bicarbonate concentration at constant pC0, (Pannier et al 1974, Pannier & Leusen 1975. The CBF was lowered to about half the normal value after intravenous infusion of about 18 ml 0.23 M Na2C03 per kg in cats with damage to the blood-brain barrier.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that p C 0~induced changes in cerebral extracellular pH readily influences the CBF in normal conditioas whereas changes in plasma bicarbonate at constant pCO2 do not, is probably related to the fact that CO, readily crosses the endothelid membrane whereas H and HCOacannot freely cross the intact blood-brain barrier. It has been demonstrated, however, that hypercapnia, o'r, in particular, damage to the blood-brain barrier induced by acute hypertension in cats, results in an increased reactivity of the cerebral blood flow to changes in the plasma bicarbonate concentration at constant pC0, (Pannier et al 1974, Pannier & Leusen 1975. The CBF was lowered to about half the normal value after intravenous infusion of about 18 ml 0.23 M Na2C03 per kg in cats with damage to the blood-brain barrier.…”
Section: Discussionmentioning
confidence: 99%
“…26 In the nine cats, CBF during inhalation of 60% FC-23 was not different from control CBF. The mean difference in CBF was -1.9 ml/100 g/min, and SD was 12.16.…”
Section: Resultsmentioning
confidence: 72%
“…On the other hand, experiments on cats have shown that CBF can be affected by changes in plasma [HCO3] when the BBB is damaged. 2 The aim of the present experiments was to study the effect of changes in the plasma [HCOi] on brain tissue [HCOi] in the presence of a lesion of the BBB, and to relate CBF in these conditions to changes in the brain tissue. The experiments were performed on rats, to allow for tissue analysis.…”
mentioning
confidence: 99%